Risk assessment of aluminum residue in drinking water of residents in Sandakan, Sabah - S., Hajira; Mohd Sham, Shaharuddin (Environmental and Occupational Health Society, 2015)
Objective: To assess the risk of aluminum residue exposure in drinking water of residents of Batu 7, Sandakan. Method: A cross sectional study was conducted to determine the health risk associated with the exposure to aluminum in drinking water among population. The study population comprised of male and female respondents, aged 18 and above whom use treated water as their main source of drinking water. A total of 100 respondents were involved in this study. Data was analysed using Statistical Package for Social Science (SPSS). Results: There was significant relationship between aluminum and pH levels of drinking water samples in the study area. There was significant difference between aluminum levels in drinking water with National Standards for Drinking Water Quality. There was no health risk of aluminum exposure among respondents, with HI<1. Conclusion: The mean of aluminum concentration was 1.03 mg/L in this study exceed the national standard of 0.2 mg/L by 5 folds, leaving a significant difference between drinking water sample and the upper safe limit. However, the Hazard Index calculated from the findings did not exceed 1. This showed that the study area was considered safe from having risk related to nervous systems, even though the aluminum concentration exceeded the upper safe limit.